KEMUDAHAN PENGGUNAAN SEBAGAI PENGGERAK UTAMA KEPUTUSAN TRANSAKSI GOPAY: EVALUASI PERAN PROMOSI DAN GENDER - Tjandra Rahardja, Conny; Ditha Ardilla (LPPM STIE YKPN Yogyakarta, 2025)
This study investigates the influence of ease of use and promotional mix on transaction decisions using GoPay, as well as the moderating role of gender. Using purposive sampling, data were collected from 103 GoPay users through Google Forms and analyzed with Hayes' PROCESS macro in SPSS 24. The findings reveal that ease of use has a significant positive effect on transaction decisions, indicating that the more user-friendly the application is, the more likely users are to engage in transactions. In contrast, the promotional mix does not show a significant effect, which is likely due to GoPay usage becoming habitual, supported by a broad digital ecosystem and the platform’s strong reputation. The moderation test also indicates that gender does not influence the relationship between ease of use and transaction decisions. These results underscore the greater importance of functional aspects and usability in e-wallet applications over promotional efforts in shaping consumer decisions.